Health literacy and loneliness among physically inactive Danes aged 18-65: a cross-sectional study - Delal Sarmanlu; Iben Rask Heuck; Helle Terkildsen Maindal; Helle Terkildsen Maindal; Michelle H. Lim; Michelle H. Lim; Knud Ryom (Frontiers Media S.A., 2024)
IntroductionBoth physical inactivity and loneliness are public health threats bringing huge costs to society and quality of life. The two health challenges often co-exist, suggesting physically inactive and lonely individuals to be a high-risk group. Health literacy as a concept is understood as a modifiable health determinant, and it has been proposed for promoting equity in future health promotion.AimThe aim of this study was to examine the association between health literacy and loneliness among physically inactive adults.MethodsA representative sample of 6,196 Danish adults, aged 18-65 years, was invited to a screening on a set of health outcomes for physical inactivity, which was based on the International Physical Activity Questionnaire-Short Form. A total of 1,033 adults were classified as physically inactive and therefore received the full questionnaire screening on a set of different health outcomes including the Health Literacy Questionnaire (HLQ) and the Three-Item Loneliness Scale (T-ILS). Two statistical approaches were applied: (1) health literacy expressed as nine different continuous variables corresponding to the domains of HLQ using logistic regressions analyses to examine the association between health literacy and loneliness; (2) health literacy expressed as nine different binary variables showing proportions of low literacy among lonely versus non-lonely participants. Statistical analyses were performed using Stata/IC version 16.1.ResultsAmong a sample of 1,010 physically inactive adults, 23.7% felt lonely with a T-ILS score below ≥7. Regression analyses predicted a negative association between health literacy and loneliness in all HLQ domains, after adjusting for gender, age, education, and occupation. Adjusted ORs ranged from 0.21 (95% CI: 0.16; 0.27) to 0.69 (95% CI: 0.57; 0.83) in domains 1-5 and 0.50 (95% CI: 0.41; 0.61) to 0.70 (95% CI: 0.55; 0.89) in domains 6-9. A similar pattern was found in the analysis with health literacy as a binary variable as the proportions of low health literacy were the highest among persons with loneliness in all HLQ domains.ConclusionEven after adjusting for sociodemographic factors, a negative association was predicted between health literacy and loneliness in physically inactive adults. This suggests that strategies for improving physical activity among inactive individuals might be more effective if they include a focus on enhancing health literacy and addressing loneliness.